Farmer organisations promote youth entrepreneurship - lessons from Zimbabwe - Kadzamira, Mariam A.T.J.; Hungwe, Shadreck; Kuipa, Prince (Technical Centre for Agricultural and Rural Cooperation, 2019)
Farmer organisations have a key role to play in encouraging and supporting the youth to thrive in the agricultural sector